A Multi-Rotor System for the Collection and Analysis of Measurements to Evaluate and Spatially Demonstrate the Pollutants in the Air. (22nd December 2015) - Molnár, András
One of the most outstanding problems of our technical age is the heavy aerial pollution. There are several well-known methods [6, 10 –15 ] that exist for large-area pollution detection, but the measurement of the exact rate of pollution in smaller areas (e.g., industrial zones or disaster-affected areas of a few square kilometres), as well as the numerical expression of changes therein, remain an unsolved problem. The main feature of the developed device is that it can provide exact measurements for a small area at low altitudes (under 500m AGL (Above Ground Level)), and it is also capable of periodical measurements between 0.0001–10 Hz. With the data analysis provided by the system, we can obtain immediate information about the pollution of the given area, as well as changes in pollution levels over time.